Service-Oriented and Cloud Computing : 8th IFIP WG 2.14 European Conference, ESOCC 2020, Heraklion, Crete, Greece, September 28–30, 2020, Proceedings /: 8th IFIP WG 2.14 European Conference, ESOCC 2020, Heraklion, Crete, Greece, September 28–30, 2020, Proceedings. (2020) - Unknown
No abstract available